2022
DOI: 10.7759/cureus.22325
|View full text |Cite
|
Sign up to set email alerts
|

Can the Reduction of Cytokines Stop the Progression of Sepsis?

Abstract: In this study, we aimed to analyze the laboratory and clinical results of cytokine hemadsorption as an immunomodulation therapy in ICU patients diagnosed with sepsis or septic shock. MethodsThe levels of procalcitonin (PCT) and C-reactive protein (CRP), determined to be indicators of infection/sepsis, and the levels of interleukins (IL-6, IL-8, and IL-10) and tumor necrosis factor α (TNFα), deemed as indicators of the cytokine storm, were compared among 32 patients before and after the hemadsorption procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similarly, in a recent prospective study by Kacar et al [16], the use of HA 330 hemadsorption for 3 days in patients with septic shock was reported to be associated with reduction in inflammatory parameters including WBC, neutrophil counts, CRP, and procalcitonin levels. Another study found that there was relationship between HA 330 treatment and reduced SOFA, PCT, and CRP levels in critically ill patients [17]. Cytosorb [18][19][20], as well as HA 330 [9,21], is frequently used in removal of cytokines via hemoperfusion in patients with sepsis/septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent prospective study by Kacar et al [16], the use of HA 330 hemadsorption for 3 days in patients with septic shock was reported to be associated with reduction in inflammatory parameters including WBC, neutrophil counts, CRP, and procalcitonin levels. Another study found that there was relationship between HA 330 treatment and reduced SOFA, PCT, and CRP levels in critically ill patients [17]. Cytosorb [18][19][20], as well as HA 330 [9,21], is frequently used in removal of cytokines via hemoperfusion in patients with sepsis/septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received hemoperfusion treatment had statistically significant decreased serum IL-6 and IL-8 levels [9]. In a recent prospective study in 32 critically ill patients receiving HA 330 therapy by Koc et al [17], serum IL-6, IL-8, IL-10, and TNF-a levels were reported to significantly decrease with hemoadsorption treatment. Our findings revealed a nonstatistically significant slightly lower decrease in inflammatory cytokines in patients treated with HA 330 than reported in the abovementioned studies, which seems to be related to larger sample size of these studies as well as the higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%